Catechol-O-Methyltransferase (COMT) Enzyme Level In Preoperative Anxiety Patients - Hamonangan Nasution, Akhyar; Lelo, Aznan (Journal of Society Medicine, 2022)
Background: Incidence of perioperative anxiety is very high, many preoperative patient experience anxiety . Thiamine acts as an essential nutrition funtionate as cofactor enzyme in most of mitochondria in brain. Brain is very susceptible to thiamine deficiency because its dependency on mitochondrial ATP production. Decreased ATP production result in inhibition of COMT activity. Low COMT levels indicated tendency for anxiety. The aim of this study is to determine the effect of thiamine in increasing COMT enzyme levels in patient with preoperative anxiety Methods : A true experiment with pretest-posttest control group and double-blind design conducted at the Department of Anesthesia and Intensive Care of University of North Sumatra in August 2019. The 60 patients were analyzed which were planned for and done an elective surgery under general anesthesia. Preoperative anxiety was measured with Amsterdam Preoperative Anxiety and Information Scale (APAIS) and COMT enzyme level measured by ELISA assays. Results : The results showed that from 64 patients had incidence of preoperative anxiety in this study was 48.3%. We found that there is significant differences in COMT enzyme levels in thiamine group compared to control (p value = 0.001). In addition, it was seen that in thiamine group had an increased COMT levels from 0.96 ng/dL to 1.78 ng/dL, while in control group there also slight increasing from 0.44 ng/dL to 0.78 ng/dL. This show that increase in COMT levels is greater in thiamine group than control group. Conclusion : Thiamine can cause increasing COMT enzyme levels in patients scheduled for elective surgery with preoperative anxiety under general anesthesia